2020
DOI: 10.4142/jvs.2020.21.e56
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the H5N1 viruses in live bird markets, Indonesia

Abstract: Background: The live bird market (LBM) plays an important role in the dynamic evolution of the avian influenza H5N1 virus. Objectives: The main objective of this study was to monitor the genetic diversity of the H5N1 viruses in LBMs in Indonesia. Methods: Therefore, the disease surveillance was conducted in the area of Banten, West Java, Central Java, East Java, and Jakarta Province, Indonesia from 2014 to 2019. Subsequently, the genetic characterization of the H5N1 viruses was performed by sequencing all 8 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Furthermore, in 2018, a reassortant event was reported between the HPAI H5N1 and LPAI virus, which has a constellation of PB1, PB2, and PA genes derived from the LPAI virus [ 7 ]. In 2020, the reassortment between the H5N1 virus clade 2.3.2 and clade 2.1.3 has been found circulating in the live bird markets in Indonesia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in 2018, a reassortant event was reported between the HPAI H5N1 and LPAI virus, which has a constellation of PB1, PB2, and PA genes derived from the LPAI virus [ 7 ]. In 2020, the reassortment between the H5N1 virus clade 2.3.2 and clade 2.1.3 has been found circulating in the live bird markets in Indonesia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of avian influenza viruses of public health concern (e.g. H5N1, H7N9, H9N2) have been detected in LBMs throughout Asia, the Middle East and Africa through longitudinal surveillance initiatives [8][9][10][11][12] . Indeed, many human cases of AIV infection have been associated with contact with poultry at LBMs 13,14 .…”
Section: Avian Influenza Ecologymentioning
confidence: 99%
“…Despite the current low number of human cases, influenza H5N1 circulation in poultry has continued unabated. Viral surveillance in LBMs has established that H5N1 circulation is occurring at levels similar to those detected during the peak period of human infections [8][9][10][11][12] . The current lack of human H5N1 cases may be linked to the dominant strain currently circulating (clade 2.3.2.1) being more 'avian-like' and not as readily able to jump the species gap to infect humans 25 .…”
Section: Current Influenza A/h5 Circulationmentioning
confidence: 99%
“…Geographical distribution, based on available geocoordinates, of confirmed HPAI A(H5N1) outbreaks in domestic birds (circles) and wild birds (triangles) (n=32); red symbols indicate outbreaks that occurred between 16 May and 15 August 2020, grey symbols indicate outbreaks that occurred between 15 August 2019 and 15 May 2020 (FAO, online-a) Information extracted from the scientific literatureAnnand et al (2020) described two A(H5N1) viruses isolated from infected chickens collected during an HPAI outbreak that took place in October 2018, in a backyard flock in south-eastern Laos. Their H5 sequences belonged to clade 2.3.2.1c and were related to other HPAI A(H5N1) viruses detected in Laos, Myanmar and Vietnam during the previous years.Following a surveillance programme from environment and poultry samples collected at live bird markets in Indonesia between 2014 and 2019,Dharmayanti et al (2020a) reported detection of HPAI A(H5N1) viruses belonging to clades 2.1.3.2a and 2.3.2.1c. Between 2017 and 2019, three clade 2.3.2.1c viruses were identified (one in 2017, from duck swab samples, and two in 2019, from Muscovy duck and chicken samples) as well as one clade 2.1.2.3a A(H5N1) virus (the latter characterised in 2018, from chicken swab samples).…”
mentioning
confidence: 99%
“…Following a surveillance programme from environment and poultry samples collected at live bird markets in Indonesia between 2014 and 2019,Dharmayanti et al (2020a) reported detection of HPAI A(H5N1) viruses belonging to clades 2.1.3.2a and 2.3.2.1c. Between 2017 and 2019, three clade 2.3.2.1c viruses were identified (one in 2017, from duck swab samples, and two in 2019, from Muscovy duck and chicken samples) as well as one clade 2.1.2.3a A(H5N1) virus (the latter characterised in 2018, from chicken swab samples).…”
mentioning
confidence: 99%